Briket Biomassa Berbahan Dasar Serat TKKS Dengan Penambahan Serbuk Pinus dan Kanji pada Sistem Screw Ekstruder Terhadap Kekuatan - Nofriady Handra (Retii, 2020)
Empty Fruit Bunches (EFB) are one of the solid wastes produced by the palm oil industry. One of the uses of EFB is as a raw material for making alternative briquettes to overcome dependence on fossil energy. In this research, the utilization of natural waste empty fruit bunches and pine bark which is processed into powder as an added material is an innovation to obtain the output of biomass briquettes for toughness and ignition quality. The addition of a certain amount of pine bark powder is an added function to see the quality of combustion. In the process of making bio-briquettes, the binder material is needed so that the briquettes are not easily crushed by 15% and the powder composition is 10%, 15%, and 20%. The tests carried out on the sample are drop test according to the ASTM D 440-86 R02 standard, and an ignition test to obtain the ash content produced from the combustion process. The results showed, at the composition of 20/15%, the ignition quality of the briquettes was higher in volume compared to the ignition of briquettes at the composition of 10/15% and 15/15%, and resulted in smoother and more uniform burning ash. On the other hand, in this composition too, the percentage of damaged briquette fibers during the drop test is 0.09%.